Challenges and Strategies: Online Learning for Elementary School Teacher Education Students - Wahyudi, Ilham; Supartinah; Nadziroh (MIMBAR PGSD Undiksha, 2023)
The existence of an online learning policy that seems suddenly has an impact on many students who are not ready to carry out the online learning process. The aim of this research is to examine perceptions, problems, and summarize students' experiences regarding strategies for resolving challenges when participating in online learning. This research is classified as a qualitative descriptive research type, with research subjects namely 61 students. Data collection in the research was carried out using observation, interviews and questionnaires, with research instruments in the form of observation and interview guidelines. The data obtained in the research was then analyzed using the Bogdan & Biklen model data triangulation technique. The data obtained is then presented in qualitative descriptive form, by adjusting the research results with the results of previous research. The results of the research analysis show that the challenges faced by students when carrying out online learning activities consist of interference from the surrounding environment, less than optimal use of the internet, students' lack of understanding of the material delivered by lecturers and reduced interaction between students and lecturers during online learning. The strategies used to face challenges for students taking part in online learning are adapted to the students' different conditions and abilities so that solutions can be found individually.